1967
DOI: 10.1002/jsfa.2740181112
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid analyses of cereal flour proteins

Abstract: Amino acid analyses have been made on flours of wheat, rye, barley, oats and maize. The overall pattern is sufficiently similar (particularly between rye and barley) to indicate a common ancestor, but significant individual differences occur. Wheat protein differs from the other four in its higher capacity for polar and H‐bonds and lower content of salt links. Other factors such as S.S interchange potential may be more important than the pattern of intermolecular forces since the latter does not change much fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…These authors found, however, high alanine content in millet, which was not observed in our investigation on Polish varieties. Higher alanine content in oats is also stated by EWART [6].…”
Section: Amimo Acid Cwtentmentioning
confidence: 69%
See 1 more Smart Citation
“…These authors found, however, high alanine content in millet, which was not observed in our investigation on Polish varieties. Higher alanine content in oats is also stated by EWART [6].…”
Section: Amimo Acid Cwtentmentioning
confidence: 69%
“…As compared with wheat, oats is rich in lysine, arginine and aspartic acid. This is in consistence with EwAw statements for oats flour [6], whereas high alanine content was not found in the Canadian oats investigated by TKACHUK et al [5].…”
Section: Comparison Of Investigated Generamentioning
confidence: 74%
“…From Ewart. 224 Results are for dehulled grain 32 days after flowering and are expressed as g/16 g N. Cysteine was determined as cysteic acid. From Cagampang et al 22i Results are for whole kernels and are expressed as g/ 100 g protein.…”
mentioning
confidence: 99%
“…This high content of hydrophobic amino acids may affect the solubility of LPYP, therefore solubility measurement was necessary. In addition, the comparison of AA contents could help to explain the phenomenon of functional properties in terms of the molecular structure …”
Section: Resultsmentioning
confidence: 99%